Scientific research methodology - Dharmapalan, Biju (Alpha Science International, 2012)
An introductory text explaining various aspects of research methodology and communication in science. It presents an outline of how to write a scientific paper and a thesis. It is also designed for the undergraduate and postgraduate students of various science subjects.